2021
DOI: 10.20524/aog.2021.0631
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolic events in patients with inflammatory bowel disease: a systematic review and meta-analysis

Abstract: Background Inflammatory bowel disease (IBD), comprising Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic inflammatory disorder of the gastrointestinal tract that has been associated with increased risk of extraintestinal manifestations, amongst which is venous thromboembolism (VTE). We assessed the risk for VTE in patients with IBD through systematic review and meta-analysis. Methods A systematic search for English language studies was conducted in Medline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
1
12
2
Order By: Relevance
“…The IBD GWAS dataset used in this study combines UC and CD, whereby we performed separate MR analyses on total IBD, UC, and CD. Unlike previous studies which reported that the risk of VTE was increased in both CD and UC patients (35)(36)(37), the MR evidence provided by this study only showed a causal relationship between UC and VTE. Notably, the meta-analysis results published by Fumery, M et al showed a significantly higher risk of VTE in UC inpatients than in CD inpatients (P = 0.0029) (14), which together with our findings suggested that UC patients may have a greater risk of VTE compared with CD patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The IBD GWAS dataset used in this study combines UC and CD, whereby we performed separate MR analyses on total IBD, UC, and CD. Unlike previous studies which reported that the risk of VTE was increased in both CD and UC patients (35)(36)(37), the MR evidence provided by this study only showed a causal relationship between UC and VTE. Notably, the meta-analysis results published by Fumery, M et al showed a significantly higher risk of VTE in UC inpatients than in CD inpatients (P = 0.0029) (14), which together with our findings suggested that UC patients may have a greater risk of VTE compared with CD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The IBD GWAS dataset used in this study combines UC and CD, whereby we performed separate MR analyses on total IBD, UC, and CD. Unlike previous studies which reported that the risk of VTE was increased in both CD and UC patients ( 35 37 ), the MR evidence provided by this study only showed a causal relationship between UC and VTE. Notably, the meta-analysis results published by Fumery, M et al.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The prevalence of thromboembolic events among IBD patients was found to be 1.1%, mostly in the interval resolution middle and left portal vein and inferior mesenteric vein. The thromboembolic events noted were thrombosis (0.5%) and DVT (0.5%), and similar findings were reported in the parallel study conducted by Arvanitakis et al, in which the prevalence was found to be between 1.3% and 7.7% [11]. Also, one congruent study reported a similar prevalence [8].…”
Section: Discussionsupporting
confidence: 85%
“…First, increased cellular attachment to the vascular inner surface, in addition to the provoked hypercoagulable state in the setting of IBD (37), induces or accelerates atherosclerosis and ultimately results in a higher risk of thrombosis events (38). Arvanitakis et al, in a recent meta-analysis, exposing the 2-fold increased risk of venous thromboembolism in patients with IBD, emphasized prophylaxis and primary prevention importance (39). Second, a thrombus formation interceded by atrial fibrillation during the active phase of IBD was illustrated by Kristensen et al (40).…”
Section: Atherosclerosis and Plaque Formationmentioning
confidence: 99%